Cyclist performance assessment based on WSN and cloud technologies - Dias, A. C.; Postolache, O. (2018 International Conference and Exposition on Electrical And Power Engineering, EPE 2018, 2018)
The mobility in the modern cities become a big issue and the usage of bicycles represent one of the solutions. At the same time Bike Share services appear that increased the motivation of the users to use bicycles. In this context, the article presents a distributed sensing system for cyclist’s training monitoring materialized by a Wireless Sensor Network (WSN), with Internet connectivity. The WSN sensing nodes are mounted on the bicycle and the cyclist himself and provide information that can be used to improve the cyclist’s performance. The coach can monitor and evaluate the athlete performance and may act to adapt the training sessions considering also other elements such as health status condition. The information coming from the WSN nodes is uploaded, through an Internet connection, to the Firebase platform. The data can be accessed through a developed Android mobile application that also allows the configuration of the training route. The effectiveness of the proposed system was experimentally tested and several results are included in the paper.